Case report: First diagnosis of Fabry disease in North Macedonia in a patient presenting with kidney failure on hemodialysis - Gjorgjievski, Nikola; Karanfilovski, Vlatko; Arsov, Todor; Vidimliski, Pavlina Dzekova; Andreevska, Galisna Severeova; Selim, Gjulshen; Dejanov, Petar; Jordanova, Vasilena; Marinova, Ivelina; Paskalev, Emil; Nikolov, Igor G. (Frontiers in Genetics, 2024)
Introduction Fabry disease is a rare X-linked lysosomal storage disorder caused by α-galactosidase A (α-Gal A) deficiency. Reduced or absent enzyme activity causes progressive lysosomal accumulation of globotriaosylceramide (Lyso-Gb3) in various cells throughout the body to trigger inflammation and fibrosis. Case description We present the first familial case of Fabry Disease in North Macedonia identified based on clinical manifestations and confirmed through enzyme, biomarker, and genetic tests. The index case in the family was a 45-year-old male undergoing hemodialysis therapy. He has had chronic burning uncontrolled limb pain since childhood, intermittent abdominal cramps, anhidrosis, and hypertension. The constellation of clinical presentations accompanied by similar symptoms in close family members prompted the enzyme, biomarker, and genetic analyses for Fabry disease. Genetic testing identified a known pathogenic GLA missense variant c.443G>A or p.(Ser148Asn) in the hemizygous state. Subsequent family studies allowed identification of another hemizygous male and five heterozygous female carriers affected by this X-linked disorder. Conclusion We report identification of the first familial case of Fabry disease in North Macedonia and describe the phenotype associated with the Ser148Asn GLA variant. Greater awareness of this rare disease linked to continuous medical education is crucial for timely diagnosis and treatment.